PENGARUH WORK-FAMILY CONFLICT DAN ROLE AMBIGUITY TERHADAP STRES KERJA ANGGOTA KEPOLISIAN SEKTOR KEDIRI DI TABANAN (Studi pada Anggota Kepolisian Sektor Kediri di Tabanan) - Dharmapatni, I Gusti Ayu Trisna; Mujiati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.11.TAHUN 2019DO - 10.24843/EEB.2019.v08.i11.p02, 2019)
The high demands of work for members of the police, the problems that are very vulnerable are experienced, namely the emergence of work stress, family problems and unclear roles in the task. These problems cause members of the police often to feel loss of concentration in their duties, often feeling exhausted at work and often absent from work. The purpose of this study was to find out Work-family Conflict and Role Ambiguity towards work stress on members of the Kediri Sector Police in Tabanan. The method of determining the sample in this study using the saturation sample method, where respondents numbered 72 members of the Kediri Sector Police in Tabanan. Data collection is done by distributing questionnaires to measure 9 indicators using a 5-point Likert scale. The data analysis technique used for this study is multiple linear regression. From the results of the analysis, this study shows that Work-family Conflict has a positive and significant effect on the work stress of members of the police. Role Ambiguity has a positive and significant effect on the work stress of police members. Suggestions for the Kediri Sector Police Department should pay attention to the work time of members so that they have free time with family and a clear work role in carrying out their duties to members of the police in order to achieve organizational.